Чучело: [сказка] / Валентина Кучеренко ; [художник Е. В. Черняева] - Кучеренко Валентина (Сказки для малышей, 2014)
Экземпляры: ф.17 (20160119) / Инвентарный номер: бр / Цена: 17.00 / Авт.знак: К 95 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6